2020
DOI: 10.3390/cells9061396
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Immune Reconstitution after Alemtuzumab Therapy in Multiple Sclerosis

Abstract: Alemtuzumab is a monoclonal antibody that binds to CD52, a protein present on the surface of mature lymphocytes, but not on the stem cells from which these lymphocytes are derived. It is currently used as an immune reconstitution therapy in patients with relapsing–remitting multiple sclerosis. Alemtuzumab treatment is an intermittent infusion that induces long-term remission of Multiple Sclerosis also in the treatment-free period. After the robust T and B cell depletion induced by alemtuzumab, the immune syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 100 publications
(187 reference statements)
1
15
0
Order By: Relevance
“…The ideal dose of DAC is a trade-off between antigen annihilation and a reduction in damaged ODC. Drug efficacy must occur with a consideration of the protection from external antigens to minimize the risk of secondary infections - sometimes with serious adverse effects - that often accompany immuno-suppressive therapies in MS [ 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The ideal dose of DAC is a trade-off between antigen annihilation and a reduction in damaged ODC. Drug efficacy must occur with a consideration of the protection from external antigens to minimize the risk of secondary infections - sometimes with serious adverse effects - that often accompany immuno-suppressive therapies in MS [ 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… 39 On the other hand, faster repopulation of T-memory cells from the pool escaping depletion, rather than naïve T cells, may contribute to secondary autoimmunity. 40 , 41 …”
Section: Biology Of Anti-cd52 Therapymentioning
confidence: 99%
“…In the literature, there is scarce information about vaccination in patients treated with alemtuzumab. Rolla et al 41 found that despite induced B lymphopenia, alemtuzumab appeared to have no effect on immunoresponses to vaccines. RRMS patients treated with that drug maintained humoral immunomemory and an ability to develop an immunoresponse against such vaccines antidiphteria, antitetanus, antipoliomyelitis, type B anti– Haemophilus influenzae , anti meningococcus C and antipneumococcal polysaccharide.…”
Section: Alemtuzumab and Vaccinationmentioning
confidence: 99%
“…For alemtuzumab, herpes prophylaxis with acyclovir is recommended for 2 years or until the CD4 + T cell count is at least 200 cells per microliter. An ongoing multicenter explorative phase IV study [ 242 , 243 ], aims to provide deeper insights into the immunological changes in alemtuzumab-MS treated patients and eventually identify biomarkers for treatment efficacy and safety.…”
Section: Monitoring Of Adverse Eventsmentioning
confidence: 99%